Twinned Tungsten Carbonitride Nanocrystals Boost Hydrogen Evolution Activity and Stability. Issue 19 (4th April 2019) - Kou, Zongkui; Wang, Tingting; Wu, Haijun; Zheng, Lirong; Mu, Shichun; Pan, Zhenghui; Lyu, Zhiyang; Zang, Wenjie; Pennycook, Stephen J.; Wang, John
Abstract: Synergistic integration of two active metal‐based compounds can lead to much higher electrocatalytic activity than either of the two individually, due to the interfacial effects. Herein, a proof‐of‐concept strategy is creatively developed for the successful fabrication of twinned tungsten carbonitride (WCN) nanocrystals, where W2 C and WN are chemically bonded at the molecule level. High‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) and X‐ray absorption fine structure (XAFS) spectroscopy analyses demonstrate that the intergrowth of W2 C and WN in the WCN nanocrystals produces abundant N–W–C interfaces, leading to a significant enhancement in catalytic activity and stability for hydrogen evolution reaction (HER). Indeed, it shows 14.2 times higher and 140 mV lower in the respective turn‐over frequency (TOF) and overpotential at 10 mA cm −2 compared to W2 C alone. To complement the experimental observation, the theoretical calculations demonstrate that the WCN endows more favorable hydrogen evolution reaction than the single W2 C or WN crystals due to abundant interfaces, beneficial electronic states, lower work function, and more active W sites at the N–W–C interfaces. Abstract : Twinned tungsten carbonitride nanocrystals are synthesized by pyrolyzing a novel W/Zn bimetal imidazolate frameworks precursor with uniformly distributed W, N, and C. It is demonstrated to be a highly active electrocatalyst for hydrogen evolution reaction (HER) by both theoretical calculations and experimental observations, due to the active W sites at the abundant N–W–C interfaces.